Наукові аспекти методу визначення консервантів у олієжировмісних продуктах - Левчук, Ірина Володимирівна; Кіщенко, Володимир Анатолійович; Тимченко, Валентина Кузьмівна; Куниця, Катерина Вікторівна; Арутюнян, Тетяна Володимирівна (Харківський державний університет харчування та торгівлі, 2016)
Наведено результати досліджень щодо визначення консервантів у маргаринах, спредах, майонезах методами високоефективної рідинної хроматографії (ВЕРХ) і капілярного електрофорезу (КЕ). Визначено особливості пробопідготовки, умови хроматографічного розділення, діапазон вимірювань сорбінової та бензойної кислот під час застосування методів. Сформульовано практичні рекомендації щодо використання методів ВЕРХ і КЕ в технохімконтролі олієжировмісних продуктів.

The present study investigates the possibility of using high performance liquid chromatography (HPLC) and capillary electrophoresis (CE) to determine mass fraction of preservatives (benzoic acid, sorbic acid and mixtures) in oil and fat emulsion products – margarines, spreads, mayonnaise. It was noted that food supplements (and, hence, and preservatives) are hazards of food quality. The conditions of sample preparation, the translation associated with the need of preservatives in water-soluble form, removing proteins that prevent the definition, and the modified starch in low-fat products. It is shown that the retention time of benzoic and sorbic acids depends on the pH of the eluting buffer. It is found that the selective separation of a mixture of these acids, which is accompanied by clear lines of the peaks in the chromatogram, is achieved at pH = 3,7–3,8. Identification of a preservative in the form of oil products is made by means of UV spectra of sorbic and benzoic acids. The measurement range of the mass fraction of preservatives in oil products by HPLC is 2–200 mg/dm3. It is recommended to use the results of this research for the development of appropriate national standard and modern schemes of technochemical control of finished products in the production of margarine and mayonnaise. It is shown that the method of capillary electrophoresis can be used to determine low concentrations of preservatives in mayonnaises and salad dressings exchange HPLC as capillary is easily restored after the starch adsorption, washing with acid and alkali, and the adsorbent column just fails. Despite some disadvantages associated with a relatively small measuring range (2–200 mg/dm3) and the complexity of the control of electroosmotic flow, to date method of capillary electrophoresis is the most promising in the study of ionic compounds. After further investigation of the sorption and ionic processes and validation techniques capillary electrophoresis can be used tehnochemkontrol oil products as a method of control of preservatives.
Scientific aspects of the method for the determination of preservatives in fat-containing products
Keywords: харчові добавки; капілярний електрофорез; високоефективна рідинна хроматографія; сорбінова кислота; бензойна кислота; хімічна промисловість; food additives; preservatives; fat-containing products; high-performance liquid chromatography; capillary electrophoresis